TINDAK TUTUR ILOKUSI IKLAN MINUMAN SUSU PADA CHANNEL YOUTUBE IKLANESIA HD - Meika, Yesinta Yesinta; Muzammil, Ahmad Rabi’ul; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research article aims to analyze illocutionary speech acts according to Searle's theory. The research method used is descriptive in qualitative form. The research data source is milk drink advertisements on the IKLANESIA HD YouTube channel. The collection technique is documentary, namely focusing attention through analyzing and interpreting written materials such as notes and texts expressed in videos, and writing tools. Data research tools are article researchers who act as compilers, data collectors and notification of research results. A tool in the form of a telephone grip is a tool used to watch milk drink advertisements on YouTube. Books and stationery are used to record words, sentences or advertising utterances watched on YouTube and then analyze the illocutionary speech acts. Data validity testing techniques include observation, triangulation and reference adequacy. The results of data analysis show that the types, utterances, and functions of illocutionary acts in milk drink advertisements on the IKLANESIA HD YouTube channel consist of 5 types of illocutionary speech acts according to Searle's theory, namely assertive illocutionary, directive illocutionary, commissive illocutionary, expressive illocutionary and declarative illocutionary.